THE INFLUENCE OF E-PROMOTION, VIRAL MARKETING, AND SOCIAL PROOF ON PURCHASING DECISIONS AT E-COMMERCE SHOPEE IN SIDOARJO - Khoironi, Affan; Sari, Dewi Komala; Febriansah, Rizky Eka (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The purpose of this study is to ascertain how social proof, viral marketing, and e-promotion affect consumer choices. This study's methodology makes use of quantitative techniques. Purposive sampling was the method employed in this study, which had 96 respondents in total. Questionnaires were sent as part of the data-gathering strategy. Multiple linear regression analysis, traditional assumption test analysis, and hypothesis testing using theSPSS 26 application analysis tool is an example of a data analysis methodology. This study may draw a number of conclusions from the testing and discussion outcomes, including the following: E-promotion, viral marketing, and social proof all affect e-commerce purchase decisions. Sidoarjo's Shopee. Keywords: E-Promotion; Viral Marketing; Social Proof; Purchase Decision